The Influence of Product Quality and Price on Customer Satisfaction in Chicken Tangan Mas Salam Cikrang West Java - Nurul Atikah, Nurul Atikah; Rushadiyati; Nurminingsih; Asim (LPPM Universitas Respati Indonesia, 2023)
This study aims to determine the effect of product quality and price on customer satisfaction in soft bone chicken Mas Salam Cikarang, West Java. The independent variables in this study are product quality and price. While the dependent variable is customer satisfaction variable. Research using quantitative methods. The sample in this study were customers at Mas Salam Soft Bone Chicken, Cikarang, West Java. Data collection was carried out by distributing questionnaires directly to 65 respondents. Statistical method using SmartPLS 3, with statistical test hypothesis testing t. The results of this study indicate that product quality has a positive and significant effect on customer satisfaction. Price has a positive and significant effect on customer satisfaction. Keywords: Product Quality, Price and Customer Satisfaction